149k views
3 votes
Complete the square for the equation below.
x2 - 6x = 0
x2 - 6x + 9 = 0 + 9

Complete the square for the equation below. x2 - 6x = 0 x2 - 6x + 9 = 0 + 9-example-1

2 Answers

1 vote

Explanation:

The first space right next to the x at the top would be -3.

The space below that last answer and above the -9 would be -3x. The space below x^2 would also be -3x.

User Jorge Martinez
by
5.2k points
2 votes

Answer:

1: x = 6

x = 0

2: x = 6

x = 0

Explanation:

1: Pulling out like terms :

2.1 Pull out like factors :

x2 - 6x = x • (x - 6)

Equation at the end of step 2 :

x • (x - 6) = 0

Step 3 :

Theory - Roots of a product :

3.1 A product of several terms equals zero.

When a product of two or more terms equals zero, then at least one of the terms must be zero.

We shall now solve each term = 0 separately

In other words, we are going to solve as many equations as there are terms in the product

Any solution of term = 0 solves product = 0 as well.

Solving a Single Variable Equation :

3.2 Solve : x = 0

Solution is x = 0

Solving a Single Variable Equation :

3.3 Solve : x-6 = 0

Add 6 to both sides of the equation :

x = 6

2: Same thing

Hope this helps

User MichaelAdam
by
4.9k points